Sains et saufs : petit manuel de lutte contre l'homophobie à l'usage des jeunes - Dorais, Michel; Verdier, Éric (VLB, 2005)
Section: 166, [10] pages ; 19 cm
Keywords: EDI; LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; identités LGBTQIA2+; intervention sociale; justice sociale; premier cycle; psy4910; pédagogie; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; violences

Whose Culture Has Capital? A Critical Race Theory Discussion of Community Cultural Wealth - Yosso, Tara J. (Race, Ethnicity and Education, 2005)
This article conceptualizes community cultural wealth as a critical race theory (CRT) challenge to traditional interpretations of cultural capital. CRT shifts the research lens away from a deficit view of Communities of Color as places full of cultural poverty disadvantages, and instead focuses on and learns from the array of cultural knowledge, skills, abilities and contacts possessed by socially marginalized groups that often go unrecognized and unacknowledged. Various forms of capital nurtured through cultural wealth include aspirational, navigational, social, linguistic, familial and resistant capital. These forms of capital draw on the knowledges Students of Color bring with them from their homes and communities into the classroom. This CRT approach to education involves a commitment to develop schools that acknowledge the multiple strengths of Communities of Color in order to serve a larger purpose of struggle toward social and racial justice.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; sciences de l'éducation; sex2283; thématiques; théorie critique de la race

Peut-on enseigner le féminisme à l’Université ? - Zaidman, Claude (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2005)
Une des façons d'interpréter le titre de ces journées est de s'interroger sur la transmission entre les générations c'est-à-dire sur la relève en Etudes féministes. Je suis heureuse de pouvoir constater, grâce à ces journées et aux journées précédentes organisées par EFiGiES avec l'aide du RING, à quel point nous pouvons être rassurées sur ce point : il existe une relève et, qui plus est, une relève qui innove tant dans les thématiques que dans les façons de s'organiser et de travailler.
Keywords: 2000 à aujourd'hui; 2000-2009; SAC; approches et analyses; justice sociale; pédagogie; périodes historiques; ressource en ligne; thématiques; université